2011
DOI: 10.1159/000331429
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Residual Cardiovascular Risk in Patients on Statin Therapy for Primary Prevention

Abstract: Background: Low-density lipoprotein cholesterol-lowering therapy is an important aspect of primary prevention of cardiovascular disease (CVD). Statins are the most widely used drug therapy for achieving low-density lipoprotein goals based on an individual’s 10-year risk. However, substantial risk of CVD events still exists even when a person is on statins. We sought to explore the predictors of future CVD events in individuals on statins with no pre-existing CVD. Methods: The analysis was done on subjects who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Indeed, Dhaliwal et al showed in a cohort study with subjects with no previous diabetes, heart attack, or stroke that WC and waist-to-hip ratio (WHR) both independently predicted CV deaths, whereas BMI did not have any predictive value ( 181 ). CRP, marker of inflammation, did not differ between the group that experienced CVD and the group without CVD, suggesting that WC is independently associated with CVD regardless of inflammation ( 182 ). However, abdominal obesity was associated with inflammation since adipose tissue was considered to generate inflammatory cytokines leading to a higher inflammatory profile in obese individuals ( 183 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Indeed, Dhaliwal et al showed in a cohort study with subjects with no previous diabetes, heart attack, or stroke that WC and waist-to-hip ratio (WHR) both independently predicted CV deaths, whereas BMI did not have any predictive value ( 181 ). CRP, marker of inflammation, did not differ between the group that experienced CVD and the group without CVD, suggesting that WC is independently associated with CVD regardless of inflammation ( 182 ). However, abdominal obesity was associated with inflammation since adipose tissue was considered to generate inflammatory cytokines leading to a higher inflammatory profile in obese individuals ( 183 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…In patients being treated with statin drugs for primary prevention, a number of predictors for residual risk have been identified, including waist circumference, large artery elasticity index, homocysteine, and coronary artery calcification 404. In the large JUPITER trial, statin-treated patients with low LDL cholesterol but high C-reactive protein levels had residual risk that was unrelated to either HDL cholesterol or triglyceride concentrations 139,140.…”
Section: Nonlipid Determinants Of Residual Riskmentioning
confidence: 99%
“…The markers generally measured for diagnosing of atherosclerosis are lipid parameters of the blood, in particular cholesterol [ 5 ]. Even though the direct link between the reduction of cholesterol and the regression of atherosclerosis is not unarguably established [ 6 , 7 , 8 ], cholesterol is still the key target parameter in the existing anti-atherosclerotic therapy [ 9 ]. It is worth noting here that the obtained data about a relation of apolipoproteins to risk scores led to slight improvement in cardiovascular disease risk prediction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%